YIA4 C Jun N-terminal kinase promotes endothelial activation at atherosclerosis-susceptible sites by enhancing expression of NF-κB transcription factors. Issue 17 (26th August 2010) - Cuhlmann, Simon; van der Heiden, Kim; Zakkar, Mustafa; Chaudhury, Hera; Luong, Le Anh; Mason, Justin; Haskard, Dorian O; Carlsen, Harald; Krams, Robert; Evans, Paul C
Abstract : Atherosclerosis develops predominantly at branches and bends in arteries that are exposed to disturbed flow which exerts low, oscillatory shear stress on endothelial cells (ECs). We demonstrated that c-Jun N-terminal kinase (JNK) is activated in ECs at atherosusceptible but not atheroprotected sites. Transcriptome profiling of cultured ECs treated with a pharmacological inhibitor revealed that JNK functions as a positive regulator of NF-κB transcription factors, which promote inflammation by inducing inflammatory molecules (eg, VCAM-1). This observation was confirmed by silencing of JNK1 and ATF2 (a downstream transcription factor), which led to reduced NF-κB expression in cultured ECs. We validated our findings by demonstrating that EC expression of NF-κB and VCAM-1 and the accumulation of CD68-positive macrophages was elevated at atherosusceptible sites compared with atheroprotected sites in aortas of wild-type mice. Genetic deletion of JNK1 suppressed NF-κB and VCAM-1 expression, and reduced macrophage accumulation at the atherosusceptible site, indicating that JNK1 positively regulates NF-κB expression and inflammation. To establish a causal relationship between shear stress and JNK activity, we altered blood flow in the murine carotid artery by placing a constrictive cuff. We observed that low, oscillatory shear stress can enhance JNK activity, NF-κB and VCAM-1 expression in ECs and promote macrophage accumulation in arteries. We conclude that JNK1-ATF2 signalling promotes EC activation and inflammation at atheroprone sites exposed to low, oscillatory shear stress by enhancing NF-κB expression. Our findings illuminate a novel level of cross-talk between the NF-κB and JNK signalling pathways that may influence the spatial distribution of atherosclerotic lesions.